The graphical method and learning in the domain and range of functions in students of the career of mathematics and physics of the UNHEVAL-2014 - Paragua Morales, Melecio (2017)
The problem that has been detected in the Specialty of Mathematics and Physics at UNHEVAL is that students determine the domain and range of functions analytically with much difficulty; this is indeed a very worrisome problem since they will be teaching Math and Physics without enough skills at basic levels where students are in formation and discovering the foundations of Maths; which is likely to be one of the reasons of many deficien- cies in students at basic leves.Because of what has been said and to try to decrease the problem of learning domain and range of functions, in this research it is been proposed the application of the graphical method with the Geogebra software; hence the final report has been designed as follows: Chapter I includes everything related to the research question as: description of the problem,formulation of the research problem, objectives, hypothesis, justification and importance, feasibility,limitations, etc.Chapter II includes the theoretical framework, where is considered: the background of the research,the basic theories and conceptual definition of terms used in the research.Chapter III, in this part is considered everything about the methodological framework of theresearch, which are: the type of research, design and layout, population and sample, data collectioninstruments, and techniques for the analysis and processing data.Chapter IV, is considered the results of the fieldwork, properly processed with statistical analyzer; inthis part it is shown the application of descriptive and inferential statistics with statistical hypothesistest for the media differences that allowed the contrast of the overall objective or general hypotheses.Then it appears the discussion of results where is analyzed what was found during the field work, andit is contrasted with references; also there are findings, suggestions, bibliography and appendices.